Benthic foraminifera as bioindicators for assessing reef condition in Kāne'ohe Bay, O'ahu, Hawai'i - Mathes, Gregor H.; Steinbauer, Manuel J.; Cotton, Laura (Pacific Conservation Biology, 2022)
Context: Tropical coral reef environments provide a wide variety of goods and ecosystem services but are experiencing growing pressure from coastal development and tourism. Assessing the status of reef communities along gradients of human pressure is therefore necessary to predict recovery and resilience capacity of reefs. Aims: First, to determine the overall water quality in Kāne'ohe Bay, O'ahu, Hawai'i, by employing a low-cost monitoring approach for anthropogenic stress on coral reef areas. Second, to assess the suitability of the monitoring approach to complement existing monitoring programmes. Methods: Sediment samples containing benthic foraminifera were used to determine water quality and stressor sources in Kāne'ohe Bay, O'ahu, Hawai'i, by applying the Foram Index (FI) and Bayesian regression analysis. The FI is based on relative abundance of functional groups of larger benthic foraminifera. Key results: Overall water quality in Kāne'ohe Bay may support active growth and recovery of coral reefs in the northern sector but deteriorates around Kāne'ohe City. Conclusions: Benthic foraminifera can be used as bio-indicators in Hawaiian reefs, providing an easy and fast-to-apply method for assessing short-term changes in water quality and stress sources. Implementing benthic foraminifera studies within existing long-term monitoring programs of Hawaiian reefs can be beneficial for conservation efforts. Implications: Within a historic context, our findings illustrate the modest recovery of an ecosystem following pollution control measures but highlight the need of conservation efforts for reef environments adjacent to major human settlements.
CRIS-Team Scopus Importer:2022-05-13
Keywords: anthropogenic stress; assessment; coral reef; corals; foram index; marine; monitoring; pollution; reef crisis; reef health; water quality